PRECEDENT TEXTS REFLECTING THE POST- REVOLUTIONARY PERIOD DURING STUDYING M. A. BULGAKOV’S “DOG’S HEART” AT LITERATURE LESSONS IN THE 8TH FORM (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-158-168This article examines the concept of “precedent text”, that is important for forming student’s national identity and their cultural connection to their homeland. The author reviewing the history of the issue pays attention at its relevance in the field of literature teaching methodology. Studying precedent texts at literature lessons allows students to immerse themselves in the historical context of a work of art and contributes to a more detailed understanding of the plot and the writer’s ideas. The research is based on demonstrating a system of tasks according to four stages of working with precedent texts. They contribute to the gradual incorporation of discursive units into student’s speech. In according, the tasks both present research-based and creative character in order to unlock student’s intellectual potential. As an example, the author uses work with M. A. Bulgakov’s novel “Dog’s Heart” which is studied in 8th form. The tasks are followed by historical and cultural comments that allows students not only to learn important information about the period but also to examine the satirical direction of the work. In addition, this system of tasks will allow precedent texts to be integrated into student’s mind. Working with precedent texts from M. A. Bulgakov’s novel, which has remained relevant for a century, will help students to understand this complex and contradictory period, broaden the horizons and comprehend the intent of a work that addresses timeless themes. Key words: precedent text, literature lesson, M. A. Bulgakov, “Dog’s Heart”, postrevolutionary period, modern school literary education